Influence of the sodium fluoride on the development and survival of the loach embryos - Grytsaj, I. R.; Mandzynets, S. M.; Bura, M. V. (Biophysical Bulletin, 2022)
Background: The study of fluoride effects at the cellular level is still essential for biophysics, medicine, and ecology as one of the most common environmental pollutants. Its impact on embryonic objects is poorly understood.Objectives: The aim of the work was: 1) to study the effect of sodium fluoride (in the minimum concentration to inhibit growth) on the morphological development of loaсh embryos; 2) evaluation of the degree of survival of embryos in the presence of sodium fluoride in the incubation medium and determination of the coefficient Ks.Materials and methods: Ovulation in loach females (Misgurnus fossilis L.) was stimulated by intramuscular injection of female chorionic gonadotropin (500 units), eggs were obtained by 36 h after stimulation, fertilized in Petri dishes with a suspension of sperm according to Neifach A. A. The stages of development were observed visually used a binocular microscope MBS-9 with a photo camera. The experimental embryos were incubated in Goltfreter's solution with the addition of sodium fluoride to a final minimum concentration to inhibit growth of 500 μmol/l.Results: Sodium fluoride inhibits the development of loach embryos and leads to developmental defects. The noticeable developmental defects caused by sodium fluoride were a reduction in the size of the larvae's head and tail, low body pigmentation, changes in the eye diameter, and embryonic touch reflex. As a result of the accumulation of fluoride in embryonic cells, on the third day of development, embryonic mortality increased to 88,9%. On 12 days under the action of sodium fluoride, the total number of larvae was about 2%.Conclusions: The ability of NaF to act as a direct teratogen was tested on the cold-blooded embryo model, the same effect was found by other investigators on the FETAX model. The possibility that sodium fluoride may cause toxic and/or neuromuscular developmental defects in human embryos also should be considered. Avoiding excessive getting of fluoride in the body by limiting the consumption of foods or beverages high in fluoride, the use of fluoride in dental care products, etc. requires detailed assessment.